Zero-carbon ammonia technology pathway analysis by IPAC-technology model in China. (10th May 2023) - Xiang, Pianpian; Jiang, Kejun; Wang, Jiachen; He, Chenmin; Jiang, Weiyi; Chen, Sha
Abstract: After China's Carbon Peaking before 2030 and Carbon Neutrality before 2060 targets announced, there is strong need to figure out transition pathways in some industrial sectors which is difficult to make deep cut of CO2 emission. This study make effort to present feasibility of zero carbon production and transition roadmap for China's ammonia industry. By using IPAC-technology model, this study compiled the production technologies, in-effect policies, and projects-in-pipeline of the ammonia industry, to figure out various technology pathways in sector, explored high/medium/low solar LCOE scenarios, and investigated the impacts of carbon price policy on the transition pathway. From this study we could see that China's ammonia industry carbon emissions peak before 2020 and it is possible to achieve net zero emissions by 2050. The results also indicated that all zero-carbon transition technology pathways could be identified over four periods from 2020 to 2050 and electrolysis technology could dominate ammonia supply and help to achieve zero carbon production as early as 2038 in the low LCOE scenario. The production costs output from our model showed that zero-carbon ammonia could be cheaper than conventional ammonia as early as 2030. Even in the high LCOE scenario, ammonia price could be 562 yuan/tNH3, which is much lower than current price, 2652 yuan/tNH3 . Carbon price policy has small effect in the transition. All our preliminary results supported the formulation of clean production and sustainable development measures and policies for the ammonia industry in China. Graphical abstract: Image 1 Highlights: The ammonia industry would achieve carbon neutral before 2050 in China. CO2 emissions of China's ammonia industry peak before 2020. Both PEM and HTGC are crucial for the decarbonization of the ammonia industry. There is a tradeoff between the timing and cost efficiency in the decarbonization. Carbon price policy has limited effect.